1985
DOI: 10.1073/pnas.82.11.3829
|View full text |Cite
|
Sign up to set email alerts
|

Membrane knobs are required for the microcirculatory obstruction induced by Plasmodium falciparum-infected erythrocytes.

Abstract: We have studied the pathophysiology of the vascular obstruction induced by Plasmodumfalkiparum-parasitized erythrocytes with the use of an ex vivo microcirculatory preparation perfused with red cells infected with knobless and knobby dones of the FCR-3 strain. We find that parasitized erythrocyte membrane knobs are indispensable for the generation of the circulatory obstruction. Uninfected erythrocytes incubated in culture and erythrocytes infected with early or late forms of the knobless dones or the early fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 16 publications
5
72
0
Order By: Relevance
“…Previously, similar fixation and embedding in LXR112 was used to study the TEM of knob and knobless P. falciparuminfected erythrocytes. 47 The ultrastructure findings of the apical complex structures required new fixation and embedding methods and materials. It is noteworthy to observe that the apical end of the mature ookinete protrudes as a sucker-like structure, which might enable effective attachment and targeted secretion of enzymes, such as proteases and chitinases, to dissolve down peritrophic matrix (PM) barrier as previously visualized.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, similar fixation and embedding in LXR112 was used to study the TEM of knob and knobless P. falciparuminfected erythrocytes. 47 The ultrastructure findings of the apical complex structures required new fixation and embedding methods and materials. It is noteworthy to observe that the apical end of the mature ookinete protrudes as a sucker-like structure, which might enable effective attachment and targeted secretion of enzymes, such as proteases and chitinases, to dissolve down peritrophic matrix (PM) barrier as previously visualized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the biological function of knobs is to augment PfEMP1 adhesion under flow (Cooke et al, 2002a;Crabb et al, 1997;Raventos-Suarez et al, 1985). KAHRP interacts directly with both the cytoplasmic tail of PfEMP1 as well as components of a modified IE cytoskeleton (Magowan et al, 2000;Oh et al, 2000;Waller et al, 1999;Waller et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The KAHRP gene product is a component of the knob structure on the surface of parasitized erythrocytes that are responsible for cytoadherence (12,13). Chromosomal breakage events disrupting the KAHRP gene result in parasite mutants that are knobless and cytoadherentdeficient (14,15,16).…”
Section: Introductionmentioning
confidence: 99%